2021
DOI: 10.18433/jpps32105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ivermectin as a Potential Treatment for Mild to Moderate COVID-19: A Double-Blind Randomized Placebo Controlled Trial in Eastern India

Abstract: Background: There has been a growing interest in ivermectin ever since it was reported to have an in-vitro activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This trial was conducted to test the efficacy of ivermectin in mild and moderate coronavirus disease 19 (COVID-19). Methods: A double blind, parallel, randomised, placebo-controlled trial conducted among adult COVID-19 patients with mild to moderate disease severity on admission in a COVID dedicated tertiary healthcare of easte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…However, other studies did not report statistically significant differences in mortality ( Ravikirti and Pattadar, 2021 ), length of hospitalization ( Abdulamir et al, 2021a ) and clinical endpoints, disease progression, recovery, the occurrence of symptoms ( Okumuş et al, 2021 ). The study authors did not recommend the routine use of ivermectin in COVID-19 patients, limiting its use to a clinical trial.…”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 95%
“…However, other studies did not report statistically significant differences in mortality ( Ravikirti and Pattadar, 2021 ), length of hospitalization ( Abdulamir et al, 2021a ) and clinical endpoints, disease progression, recovery, the occurrence of symptoms ( Okumuş et al, 2021 ). The study authors did not recommend the routine use of ivermectin in COVID-19 patients, limiting its use to a clinical trial.…”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 95%
“…Just over a third of trials exposed the clinical group to another medicine (excluding those in the standard of care) such as doxycycline, azithromycin, etc. Mortality was noted across eight different reports, and in almost all of them death occurrence was more prominent in the control arm [23][24][25][26][27][28][29]. The only study whose findings were not consistent with the rest is the retrospective cohort in Peru by Soto-Beccerra et al [22] which found a higher mortality rate in the interventional group.…”
Section: Resultsmentioning
confidence: 99%
“…In their description of the study by Ravikirti et al, mortality was described as "improved" with ivermectin compared with controls "0% versus 6.9%, P 5 0.019." 1,16 However, there was no statistical difference in mortality (0/55 vs. 4/57, Fisher exact P value 5 0.12). A mortality benefit with ivermectin in severely ill patients was stated to be "of borderline statistical significance, 0% (0/11) versus 27.3% (6/22), P 5 0.052" in the description of Hashim's study.…”
Section: Kory and Marik Meta-analysesmentioning
confidence: 89%